System samogłoskowy współczesnego języka górnołużyckiego - Jocz, Lechosław (Slavia Occidentalis, 2012)
This article provides an extended synopsis of the author’s Ph.D. thesis Wokalowy system hornjoserbskeje rěče přitomnosće. The first part is devoted to selected methodology-related issues (e.g. the method of collecting recordings, approach to not adopted German words, the number of phonetic units researched). In part two, the author establishes an inventory of vowel phonemes of contemporary Upper Lusatian and the fundamental rules of reduction. Based on distribution analyses, including morpho(no)logical facts, the skill of identification and isolated pronunciation of vowel sounds as well as development trends, ten phonemes: /i, ɪ, e, ɛ, a, ɨ, ɔ, o, ʊ, u/ have been adopted in this article. In the third part, the author presents the results of acoustic research (with respect to timbre and inherent length, depending on accent and other factors).To a large extent, these results present an entirely different picture from the existing postulates based on auditive analyses. On top of that, certain linguistic universals are confirmed here. The last part offers a set of distinctive features. Following acoustic research, the author decided to adopt a binary [peripheral] feature and to apply gradual characteristics.